2022
DOI: 10.3389/fenvs.2022.955744
|View full text |Cite
|
Sign up to set email alerts
|

Research on the cultivation of green competitiveness among chinese heavily polluting enterprises under country/district environmental regulations

Abstract: The development of the world economy has caused serious environmental pollution, which has resulted in an ecological crisis. With the acceleration of economic development, China’s ecological crisis is becoming more serious. Green technology innovation is an important driving force in realizing green economic development, and heavily polluting enterprises are the key link to cultivating green technology innovation. The Porter hypothesis holds that environmental regulation has a promoting effect on enterprises’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
2
13
0
Order By: Relevance
“…For the first time, based on the quasinatural experiment of ECS-SDHM in China, our study examines the policy effect of ECSMC on corporate green innovation, and provides new perspectives and new ideas for the research on the influencing factors of corporate green innovation. Empirical research applying the multi-dimensional fixed-effects DID model found that: Firstly, ECS-SDHM can significantly improve corporate green innovation, and the policy effect has a more significant role in promoting green innovation among private listed companies, which is consistent with the conclusion of the green innovation effect of traditional environmental policies (Shen et al, 2020;Zhang T. et al, 2022). Secondly, from the perspective of corporate ESG performance, we found that the ESG performance is an important mechanism for ECS-SDHM to improve corporate green innovation, and ECS-SDHM is mainly achieved by improving the performance of environmental governance and social governance in the performance of corporate ESG.…”
Section: Conclusion and Limitationssupporting
confidence: 61%
“…For the first time, based on the quasinatural experiment of ECS-SDHM in China, our study examines the policy effect of ECSMC on corporate green innovation, and provides new perspectives and new ideas for the research on the influencing factors of corporate green innovation. Empirical research applying the multi-dimensional fixed-effects DID model found that: Firstly, ECS-SDHM can significantly improve corporate green innovation, and the policy effect has a more significant role in promoting green innovation among private listed companies, which is consistent with the conclusion of the green innovation effect of traditional environmental policies (Shen et al, 2020;Zhang T. et al, 2022). Secondly, from the perspective of corporate ESG performance, we found that the ESG performance is an important mechanism for ECS-SDHM to improve corporate green innovation, and ECS-SDHM is mainly achieved by improving the performance of environmental governance and social governance in the performance of corporate ESG.…”
Section: Conclusion and Limitationssupporting
confidence: 61%
“…3) Innovation in green equipment, which refers to continuous innovation in the utilization and modification of production equipment by enterprises for low-carbon environmental protection. 4) Innovation in green sales, indicating continuous innovation in the design, implementation, and development of product sales channels by enterprises in terms of low-carbon environmental protection [32].…”
Section: Plos Onementioning
confidence: 99%
“…In other words, the relationship between X and Y is divided by M. However, this model does not examine the function of M. Thus, in the subsequent research, I will follow the research of Hussain et al [53] and Xuezhou et al [54] to research the mediation of the sum of import and export and the unemployment rate (both are threshold variables of this study). Fourthly, many scholars, such as Zhang et al [55], have proved that green energy has a significant effect on economic development. Besides, the Chinese government announces that China will achieve carbon neutrality in 2060.…”
Section: Plos Onementioning
confidence: 99%